A new nanomatrix based on functionalized fullerene and porous bimetallic nanoparticles for electrochemical chiral sensing. (17th May 2018) - Ma, Jiao; Yang, Chengcheng; Zhu, Shu; Song, Jinyi; Fu, Yingzi
Abstract : A simple, functionalized fullerene and porous Au@Pd nanoparticle-based chiral sensor for tyrosine enantiomer recognition. Abstract : Herein, a simple and convenient chiral sensor for tyrosine (Tyr) enantiomer recognition was developed based on a simply synthesized nanomatrix, which was coupled tol -cysteine-functionalized fullerene (C60 -l -Cys), porous Au@Pd bimetallic nanoparticles (Au@Pd), and thiol-β-cyclodextrin (HS-β-CD). The nanomatrix was characterized by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), and Fourier transform infrared spectroscopy (FTIR). Electrochemical interactions between Tyr enantiomers and the nanomatrix-modified glassy carbon electrodes (GCEs) were investigated via square wave voltammetry (SWV). The results showed obvious differences between the peak currents of Tyr enantiomers, hinting that Tyr enantiomers could be effectively recognized by the sensor. This method provides a promising perspective to identify Tyr enantiomers with the advantages of simple preparation, rapid response, excellent stability, and reproducibility.